Autism Heterogeneity in a Densely Sampled U.S. Population: Results From the First 1, 000 Participants in the RI‐CART Study. Issue 3 (20th January 2020) - McCormick, Carolyn E. B.; Kavanaugh, Brian C.; Sipsock, Danielle; Righi, Giulia; Oberman, Lindsay M.; Moreno De Luca, Daniel; Gamsiz Uzun, Ece D.; Best, Carrie R.; Jerskey, Beth A.; Quinn, Joanne G.; Jewel, Susan B.; Wu, Pei‐Chi; et al.
Abstract : The objective of this study was to establish a large, densely sampled, U.S. population‐based cohort of people with autism spectrum disorder (ASD). The Rhode Island Consortium for Autism Research and Treatment (RI‐CART) represents a unique public‐private‐academic collaboration involving all major points of service for families in Rhode Island affected by ASD. Diagnosis was based on direct behavioral observation via the Autism Diagnostic Observation Schedule, Second Edition. For the first 1, 000 participants, ages ranged from 21 months to 64 years. Using Geographic Information System and published prevalence rates, the overall cohort is estimated to represent between 20% and 49% of pediatric age persons in Rhode Island with ASD, with demographics representative of U.S. Census. We observed a high rate of co‐occurring medical and psychiatric conditions in affected individuals. Among the most prominent findings of immediate clinical importance, we found that females received a first diagnosis of ASD at a later age than males, potentially due to more advanced language abilities in females with ASD. In summary, this is the first analysis of a large, population‐based U.S. cohort with ASD. Given the depth of sampling, the RI‐CART study reflects an important new resource for studying ASD in a representative U.S. population. Psychiatric and medical comorbidities in ASD constitute a substantial burden and warrant adequate attention as part of overall treatment. Our study also suggests that new strategies for earlier diagnosis of ASD in females may be warranted. Autism Res 2020, 13: 474–488 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: The Rhode Island Consortium for Autism Research and Treatment (RI‐CART) represents a unique public‐private‐academic collaboration involving all major points of service for families in Rhode Island affected by autism spectrum disorder (ASD). In this article, we provide results from the first 1, 000 participants, estimated to represent >20% of affected families in the state. Importantly, we find a later age at first diagnosis of ASD in females, which potentially calls attention to the need for improved early diagnosis in girls. Also, we report a high rate of co‐occurring medical and psychiatric conditions in affected individuals.